Konsep Pendidikan Menurut Muhammad Naquib Al-Attas dan Relevansinya dengan Sistem Pendidikan Nasional - Sri Syafa’ati; Hidayatul Muamanah (LP2M STIT Palapa Nusantara, 2020)
Education is part of the life of the community and nation to realize the ideals of the nation. So that national education activities need to be managed and organized into a means to realize national goals. This study aims to determine the concept of education according to Syed Muhammad Naquib al-Attas and its relevance to the national education system. In this research, the approach used is a qualitative approach with the type of library research. Sources of data were obtained from books and journals related to research material. The results showed that Syed Muhammad Naquib al-Attas was a very intelligent and religious scientist. Syed Muhammad Naquib al-Attas divides knowledge into 2 types, namely the science of fardu 'ain and the science of fardu kifayah. This is also similar to the sharing of knowledge in education in Indonesia, namely religious science, social science and science.